Correction: Adardour et al. Crystal Structure, DFT Calculation, and Hirshfeld Surface Analysis of the 1-(Cyclohex-1-en-1-yl)-3-(prop-2-yn-1-yl)-1,3-dihydro-2H-benzimidazol-2-one. Crystals 2023, 13, 1661 - Mohamed Adardour; Marouane Ait Lahcen; Ismail Hdoufane; Mohammed M. Alanazi; Mohamed Loughzail; Henia Bouzidi Mousser; Solenne Fleutot; Michel François; Driss Cherqaoui; Abdesselam Baouid (Crystals)
In the published work [...]